(untitled) (Rajarshi Janak University Research Journal, 2024)
The perception of bankers on green banking practices in commercial banks in the Kathmandu Valley can provide valuable insights into the current state of sustainable practices. To effectively implement sustainable practices, banks must develop policies and strategies, provide training and education, and promote green products and services. However, developing nations face challenges such as lack of infrastructure and resources. In order to investigate the perception of Green Banking in developing country like Nepal, we chose banking professionals working in the Kathmandu Valley, the capital city of Nepal. Structured questionnaires were used to collect data and PLS-SEM was used to analyze bankers’ perception on Green Banking in commercial banks of the Kathmandu Valley. A sample of 403 individuals was gathered using the KOBO toolbox from the Kathmandu Valley. Purposive sampling technique is used as a sampling technique of non-probability sampling. This study tested five hypotheses on the relationship between banking policy, daily operations, investment, and green banking practices in commercial banks in the Kathmandu Valley. Hypotheses H2, H3 and H4 are supported. The study identifies a lack of awareness among bankers in the Kathmandu Valley about green banking practices, highlighting the need for better education and training. Despite challenges such as trust issues and limited technology knowledge, green banking offers significant potential for enhancing business operations, customer loyalty, and environmental responsibility.